Targeting Unconventional Host Components for Vaccination-Induced Protection Against TB - Nemes, Elisa; Khader, Shabaana A.; Swanson, Rosemary V.; Hanekom, Willem A. (Frontiers in Immunology, 2020)
The current tuberculosis (TB) vaccine, Bacille Calmette-Guerin (BCG), is effective in preventing TB in young children, but was developed without a basic understanding of human immunology. Most modern TB vaccine candidates have targeted CD4+ T cell responses, thought to be important for protection against TB disease, but not known to be sufficient or critical for protection. Advances in knowledge of host responses to TB afford opportunities for developing TB vaccines that target immune components not conventionally considered. Here, we describe potential of targeting NK cells, innate immune training, B cells and antibodies, and Th17 cells in novel TB vaccine development. We also discuss attempts to target vaccine immunity specifically to the lung, the primary disease site in humans.